About Gamification & What Do We Use for Nowadays - Kovács, Tamás; Várallyai, László (International Journal of Engineering and Management Sciences, 2018)
By the widespread increase of new technologies, Internet has become an essential element for generation Z, however, this is not particularly surprising given the fact that over recent years different IoT solutions have become widely available, well-known and increasingly cheaper. Thus the grown up of Net Generation brings innovative solutions to the fore by which motivation is not forced to students anymore but there will be a real internal demand from their side in accordance with the age of Motivation 3.0. If this will be the case, the social issue of Homo Ludens will be also appeared in parallel to gamification [1]. Gamification nowadays is a method that become more widely used depending on field of use, thus it may meet needs of businesses and also educational institutions. The term of gamification is understood to mean those technics and methods when game elements are used in non-gaming environments [2]. Since we do not concentrate on learning during games, students will find learning a pleasure rather than an imposition and it means many could improve their skills or receive information without realizing they are actually studying. Moreover, despite the traditional learning method, the knowledge acquired this way can be used for a long time during seminars and later on labour market. Gamification plays an increasingly important role in business and also in education [3]. Students may learn more effectively and with a lower effort using gamification. As a result, this innovative approach of learning has been becoming more and more popular internationally, furthermore, motivation shortage problems also could be solved by this method [4].